Practicing oral history to connect university to community - Montoya, Fawn-Amber (Practicing oral history series, 2019)
"Practicing Oral History to Connect University to Community illustrates best practices for using oral histories to foster a closer relationship between universities and their surrounding communities. It is an important resource both for oral historians and those working to improve relationships between universities and their communities"--